Cementless total hip arthroplasty after failed internal fixation of acetabular fractures: A single center experience of 25 consecutive patients. (30th April 2020) - Do, Min Uk; Shin, Won Chul; Moon, Nam Hoon; Kang, Suk-Woong; Suh, Kuen Tak
Purpose: Total hip arthroplasty (THA) is an available surgical option for failed acetabular fracture, previously managed by open reduction and internal fixation. This study aimed to report the postoperative outcomes of cementless THA in patients with this condition. Materials and Methods: Between November 2000 and September 2016, 25 consecutive cementless THAs for failed internal fixation after acetabular fractures with a minimum follow-up of 2 years were analyzed. The mean age at the time of surgery was 58 years (36–85 years), and the time elapsed between fracture and THA was 70 months (7–213 months). Clinical and radiologic evaluations were performed on all patients. Results: Clinically, the mean Harris hip score at the last follow-up was 88 points. Walking ability recovered to pre-injury status in 92% patients, and activities of daily living recovered in 96% patients. Radiographically, none of the acetabular cups showed evidence of migration and loosening during the mean follow-up of 50 months. All cases showed stable femoral stem fixation at the last follow-up. Dislocation occurred in three cases (12%). Conclusion: Outcomes of cementless THA after failed internal fixation for acetabular fractures were satisfactory. However, a relatively high incidence of postoperative dislocation is still a concern.